2011
DOI: 10.2165/11588250-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Using QALYs in Cancer

Abstract: The objective of this paper is to examine how well the QALY captures the health gains generated by cancer treatments, with particular focus on the methods for constructing QALYs preferred by the UK National Institute for Health and Clinical Excellence (NICE). Data were obtained using a keyword search of the MEDLINE database and a hand search of articles written by leading researchers in the subject area (with follow up of the references in these articles). Key arguments were discussed and developed at an oncol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 60 publications
3
41
0
Order By: Relevance
“…Second, the questionnaire used in this study was not directed against thyroid-specific quality of life, so the specificity of our study findings may be relatively poor. For example, the EQ-5D-3L questionnaire was found not to be quite sensitive in the oncology setting, especially in situations where level of vitality is an important element27. In the context of thyroid nodules, where vitality/fatigue is the most impacted domain by hypothyroidism, the EQ-5D-3Ltool might not capture small difference in QALYs between RFA and OT.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the questionnaire used in this study was not directed against thyroid-specific quality of life, so the specificity of our study findings may be relatively poor. For example, the EQ-5D-3L questionnaire was found not to be quite sensitive in the oncology setting, especially in situations where level of vitality is an important element27. In the context of thyroid nodules, where vitality/fatigue is the most impacted domain by hypothyroidism, the EQ-5D-3Ltool might not capture small difference in QALYs between RFA and OT.…”
Section: Discussionmentioning
confidence: 99%
“…Disease-specific measures might capture more benefits than generic HRQoL measures. It has been argued that the EQ-5D and the SF-6D are too generic and insensitive to measure the main outcome of interest for less severe health problems [22,71]. When choosing a utility measure it is important to consider which method is most likely to be sensitive to the health change for the specific patient group included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to be in a health state worse than death with a negative quality index. The National Institute for Health and Clinical Excellence (NICE) in the United Kingdom recommends a set of values estimated from 3,000 members of the UK population using the time trade-off technique [22]. Other countries have estimated similar country-specific health state utility values [23].…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analytic summaries of studies that have used QALYs, however, have empirically suggested that the method may be inadequate for capturing the vital QOL issues quantitatively. 11 …”
Section: Introductionmentioning
confidence: 99%
“…For a general overview of QALYs and a discussion of different methods of selecting utilities, see the monograph by Sloan et al 12 A discussion of QALY application models in cancer is found in Cole et al 13 and a recent discussion of clinically important differences and QALYs is found in Revicki et al 3 Kilbridge 14 provides a review of the current use of QALYs in oncology (health care), and their methodological limitations are discussed by Garau et al 11 …”
Section: Introductionmentioning
confidence: 99%